The Effect of Accounting Conservatism, Capital Structure, Liquidity, Profitability, And Corporate Social Responsibility Disclosure on Earnings Quality : (Empirical Study on State-Owned Enterprises Listed on The Indonesia Stock Exchange In 2023 And 2024) - Dewa Ayu Dyah Prema Gandhi; I Gde Ary Wirajaya (International Forum of Researchers and Lecturers, 2025)
State-Owned Enterprises (SOEs) are business entities whose capital is wholly or primarily owned by the government, and in the form of Persero, partial capital participation from the private sector is permitted. Earnings quality reflects the firm’s true economic condition; therefore, it is influenced by financial conditions and the policies implemented. This study aims to examine the effect of accounting conservatism, capital structure, liquidity, profitability, and Corporate Social Responsibility (CSR) disclosure on earnings quality in SOEs listed on the Indonesia Stock Exchange during 2023 and 2024. Research data were obtained from financial statements and sustainability reports as secondary sources, and analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that accounting conservatism has a positive effect on earnings quality, whereas liquidity and profitability have negative effects. Meanwhile, capital structure and CSR disclosure show no significant effect on earnings quality. These results provide empirical insights for stakeholders in understanding the factors that influence the reliability of earnings information in SOEs.